2016
DOI: 10.1155/2016/1940456
|View full text |Cite
|
Sign up to set email alerts
|

West Africa Extreme Rainfall Events and Large-Scale Ocean Surface and Atmospheric Conditions in the Tropical Atlantic

Abstract: Based on daily precipitation from the Global Precipitation Climatology Project (GPCP) data during April–October of the 1997–2014 period, the daily extreme rainfall trends and variability over West Africa are characterized using 90th-percentile threshold at each grid point. The contribution of the extreme rainfall amount reaches ~50–90% in the northern region while it is ~30–50% in the south. The yearly cumulated extreme rainfall amount indicates significant and negative trends in the 6°N–12°N; 6°N–12°N; 17°W–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…The local percentiles were used to select the intense events at a daily timescale, in accordance with other studies carried out at continental or sub-continental scale [39][40][41]. Along the coast, mean annual precipitation shows a large range of values, from less than 900 mm at Lomé (Togo) to over 2000 mm at Axim (Ghana) and Tabou (Ivory Coast).…”
Section: Definition Of Intense Rainfall Eventsmentioning
confidence: 99%
“…The local percentiles were used to select the intense events at a daily timescale, in accordance with other studies carried out at continental or sub-continental scale [39][40][41]. Along the coast, mean annual precipitation shows a large range of values, from less than 900 mm at Lomé (Togo) to over 2000 mm at Axim (Ghana) and Tabou (Ivory Coast).…”
Section: Definition Of Intense Rainfall Eventsmentioning
confidence: 99%
“…Evidence of climate change in Nigeria has been discussed by [16], who reported increasing damage caused by wind and rainstorms, which are projected to increase in southern regions [17]. The northern part of the country has been experiencing a reduction in rainfall and an increase in the rates of dryness and heat [18,19], while the rainfall amounts have been increasing in the southern part with an irregular pattern [19,20]. Moreover, climate projections for the 21st century show a significant increase of temperature over all the ecological zones [17] which may have negative 2 Advances in Meteorology impacts on agriculture and food security.…”
Section: Introductionmentioning
confidence: 99%
“…Precisely, an important feature also observed in VIMF anomaly patterns from July to October is the westward intense anomalies over WA extending over the equatorial Atlantic Ocean. For extreme rainfall events in WA, Ta et al [100] found the contrary; VIMF is dominant to the east and it penetrates into WA mainly from the equatorial Atlantic Ocean.…”
Section: Roles Of the Sources During Extremely Dry Conditionsmentioning
confidence: 94%